Towards a Red List of the terricolous lichens of Italy. (7th July 2022) - Gheza, Gabriele; Di Nuzzo, Luca; Nimis, Pier Luigi; Benesperi, Renato; Giordani, Paolo; Vallese, Chiara; Nascimbene, Juri
Abstract: Terricolous lichens, threatened in many areas of Europe, have been greatly overlooked in conservation policies. This work provides a provisional Red List of the terricolous lichens of Italy, to favour their inclusion in conservation policies. The taxa were assigned to IUCN categories according to a simplified assessment procedure based on their rarity and past/current distribution in the administrative regions and ecoregions of Italy. We evaluated 162 species: 30 were listed as regionally extinct, 22 critically endangered, 16 endangered, 49 vulnerable, 27 near-threatened, 7 least-concern, and 11 data deficient. A quarter of the terricolous lichens of Italy is likely to be threatened, but a rigorous assessment is hindered by the scarcity of data. Further field work is needed for more precise assessments of their conservation status.